The geomorphologic response of a large pristine alluvial river to tremendous deforestation in the South American tropics: The case of the Araguaia River - Latrubesse, Edgardo Manuel (2009)
Abstract: The geomorphic response of the Araguaia River to catastrophic deforestation of the Cerrado since 1970s is discussed. With a mean annual discharge of 6,500m3/s and a drainage area of ~380,000km2, the Araguaia River is the main system draining the savannas of Central Brazil. Here, we demonstrate that the river is undergoing a substantive increase in bed load transport and changes in its geomorphology. A multi-approach methodology was used and involved detailed geomorphologic mapping for three decades (60,70,90), a budget of erosional and deposition areas using GIS, volumetric calculations, and estimations of bed load transport. Our results show that the alluvial plain is undergoing active sedimentation and 233 Mt of sediments were stored by channel activity in a reach 570km long of the middle Araguaia.. The bedload transport has increased 31% from 6.6 Mt in the sixties to 8.8 Mt in the 1990s and the channel pattern has been metamorphosed to some extent. This is an outstanding current example of short term geomorphic response to deforestation in a large pristine tropical fluvial system without direct human interventions in the channel.